Chiral Photocurrent in Parity-Violating Magnet and Enhanced Response in Topological Antiferromagnet - Hikaru Watanabe (American Physical Society, 2021)
Rectified electric current induced by irradiating light, a so-called photocurrent, is an established phenomenon in optoelectronic physics. In this paper, we present a comprehensive classification of the photocurrent response arising from the parity violation in bulk systems. We clarify the contrasting role of T and PT symmetries and consequently find new types of photocurrent phenomena characteristic of parity-violating magnets—the intrinsic Fermi surface effect and the gyration current. In particular, the gyration current is induced by circularly polarized light, and it is the counterpart of the shift current caused by linearly polarized light. This photocurrent adds a new functionality of materials studied in various fields of condensed matter physics such as multiferroics and spintronics. A list of materials is provided. Furthermore, we show that the gyration current is strongly enhanced by topologically nontrivial band dispersion. On the basis of the microscopic analysis of Dirac models, we demonstrate the divergent photocurrent response and elucidate the importance of the tilting of Dirac cones.